Громадянин у цифрових трансформаціях сучасного світу - Гарбузова, Д. С. (ХНУРЕ, 2025)
The article is devoted to the problems of coexistence of the citizen, the state and society. It is argued that the processes of globalization and digitalization of modern society contribute to the emergence of new political phenomena and social relations. The foundation of citizenship lies in an individual's legal status as a citizen. From a legal perspective, citizenship can be defined as a stable bond between an individual and the state, characterized by mutual rights and obligations. The political science approach to citizenship associates it with liberal ideas of individual human rights and with the idea of human interaction with the community and devotion to the state.
Keywords: громадянин; цифрова трансформація сучасного світу